Perancangan Alat Otomatis untuk Penyiraman dan Pemupukan Bibit Tanaman Buah - Muhammad Echan Hardinata; Nina Paramytha (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Fruit cultivation plays a crucial role in the agricultural economy, where seed quality significantly impacts productivity. Watering and fertilizing fruit plant seedlings are key aspects of ensuring healthy growth. To meet the demands of modern agriculture, an automated solution has been developed utilizing messaging application-based technology, such as Telegram. This device enables remote control of watering and fertilizing processes via the Telegram bot feature, ensuring precision and convenience. Advantages include time efficiency, optimal fertilization, and precise watering, supported by light sensors and soil moisture sensors to enhance the process. Experimental results show that this technology successfully addresses challenges related to irregular watering and fertilization. Consequently, this automated system has the potential to enhance productivity and efficiency in fruit cultivation.